Effects of continuous rate infusion of butorphanol in isoflurane-anesthetized calves - Araújo, Marcelo Augusto De; Albuquerque, Verônica Batista De; Deschk, Maurício; Trein, Thomas Alexander; Frazílio, Fabrício De Oliveira; Santos, Paulo Sergio Patto dos [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE:To assess the hemodynamic changes and bispectral index (BIS) following administration of a continuous rate infusion (CRI) of butorphanol in isoflurane-anesthetized calves.METHODS: Eight calves weighing 110 ± 12 kg were included in the study. Anesthesia was induced with 5% isoflurane in O2 delivered via face mask and maintained with end-tidal concentration of 1.4%. IPPV was set to a peak inspiratory airway pressure of 15 cmH2O and respiratory rate of six breaths minute-1. Forty minutes after the start of anesthetic maintenance, 0.1 mg kg-1butorphanol was administered intravenously, followed by a CRI of 20 µg kg-1 minute-1. Hemodynamic variables and BIS were recorded before butorphanol administration (T0), and at 10, 20, 40 and 80 minutes following the CRI. Anesthesia was discontinued after the last recording and the calves were allowed to recover. The time to sternal recumbency (SRE) and standing (ST) were evaluated.RESULTS: There were no significant differences between the moments in all hemodynamic variables and BIS. The time to SRE and ST was 9 ± 5 and 14 ± 7 minutes, respectively.CONCLUSION: The continuous rate infusion did not produce clinically relevant changes in hemodynamic or bispectral index values compared to baseline in mechanically ventilated and unstimulated calves anesthetized at 1.4% isoflurane.
Keywords: Hemodynamics, Intermittent Positive-Pressure Ventilation; Butorphanol; Anesthesia, Inhalation; Cattle